Analisa Kerusakan Pompa Progressive Cavity Pada Pengoperasian di Kolam Lumpur Scum Dengan Posisi Suction Lift - Candra, Riki; Jamaludin, Jamaludin (Motor Bakar : Jurnal Teknik Mesin, 2025)
This study aims to determine the causes of damage to a progressive cavity pump operated in a scum waste pond. The pump is installed in a suction lift position, which is a position where the pump is above the liquid surface with a height of 4 meters and a liquid viscosity equivalent to a density of 6.5%. In this pump position, the pump is required to suck the liquid before the liquid enters the stator cavity and is then pushed to the discharge pipe. A Progressive Cavity Pump, abbreviated as PCP, is a type of pump that uses the Moineau principle to work. When the rotor rotates in the stator cavities, a vacuum condition will occur in the suction pipe, so that the liquid below the pump can move into the pipe towards the stator. However, because the suction lift height is too large exceeding the standard factory specification value of 2.5 meters, and the viscosity exceeds 5%, the speed of the liquid entering the stator cavity is reduced, resulting in the pump operating in dry running conditions for a fairly long time and the stator becoming hot due to friction with the rotor. This causes the elastomer in the stator to be damaged and the pump performance becomes less than optimal